(untitled) (Balneo and PRM Research Journal, 2024)
In the modern world, technological progress has also been accompanied by an increase in traumatic suffering, including those followed by spinal cord injury. The severity of spinal cord injury requires an understanding of the physiological and psychological aspects of patient management. Spinal cord lesions impair physical capabilities and tend to reduce the quality of life, thus creating the need for psychological intervention. In order to do the magnetic resonance imaging (MRI), it has been observed that patients frequently experience distress (1) Background: The research highlights the significant influence that psychological interventions have on improving the quality of life of patients undergoing MRI, who have sustained spinal cord injury; (2) Methods: we studied 78 patients hospitalized in the Neurosurgery Clinic 2 of the "Bagdasar Arseni" Hospital for acute spinal cord injuries, in 2 groups of patients with and without psychotherapy, for which we later applied the quality of life test; (3) Results: We observe how, in 2017, SCI were more frequent in the adult male population and psychotherapeutic treatment was slightly more effective in improving QOL in male patients.; (4) Conclusions: For the 27 patients investigated by MRI and operated for SCI in the Neurosurgery Clinic 2 of the "Bagdasar Arseni" Hospital, the average quality of life was higher after the psychotherapy, both for female patients and for male patients and. The psychotherapeutic response and improved quality of life were higher in male patients.